Applied Theatre and Intercultural Dialogue Playfully Approaching Difference - Leffler, Elliot (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines applied theatre projects that bring together diverse groups and foster intercultural dialogue. Based on five case studies and informed by play theory, it argues that the playful elements of theatre processes nurture a unique intimacy among diverse people. However, this playful quality can also dampen explicit conversations about participants' cultural differences, and defer an interrogation of people's own entrenchment in systemic power imbalances. As a result, addressing these differences and imbalances in applied theatre contexts may require particular strategies. Elliot Leffler is Assistant Professor of Theatre and Performance at the University of Toronto in Canada. As an artist and a scholar, Elliot explores theatre-making as a context for intercultural, interfaith, and intergenerational dialogue. He has led theatre projects with white, black, and coloured South Africans, with Jews and Palestinians in Israel, with Kurdish and Arab Iraqis, with urban US high school students, and with racially-diverse houses of worship. His previous publications include articles in Research in Drama Education: The Journal of Applied Theatre Research, Theatre Research International, The Drama Review, Theatre Topics, and Contemporary Theatre Review. .
1. Introduction -- 2. "Stepping Out": The Physical Play and Incorporeal Dialogue of Applied Theatre Processes -- 3. Role Play: Performing Variability, Embracing Communitas, and Obsfucating Racial Tension -- 4. It's Personal: Autobiographical Stories as Catalysts for Playful Dialogue -- 5. Mythical Play: Embodying the Epic -- 6. Punctured Play: A Dramaturgy of Absorption, Interruption, and Interrogation -- 7. Epilogue.
Keywords: Theater; Performing arts; Intercultural communication; Peace; Applied Theatre; Theatre and Performance Arts; International and Intercultural communication; Peace and Conflict Studies